Mentoring Mengelola Keuangan dan Perbankan Mahasiswa Master Penerima Beasiswa NTB di Malaysia dan Polandia - Zahrah; Baiq Dinna Widiyasti; Lady Faerrosa; Isra Dewi Kuntary Ibrahim; Widia Febriana (Kreativasi : Journal of Community Empowerment, 2022)
NTB Scholarship is a program designed by the Provincial Government of West Nusa Tenggara which is intended to improve the existing human resources in the NTB through sending the best youngers to pursue their studies in country and abroad. Life as a      student in country will certainly be very different from overseas life, especially in managing finances while being an international student. Considering that, it is very essential to transfer information and to accompany what is needed before taking off. The aim is to provide an insight and how to manage finance and what they need to know in preparing for overseas life. This program of community development is carried out using an online mentoring strategy through the google meet site. The target is NTB scholarship awardees who are postgraduate students in Malaysia and Poland. The results of these activities include the emergence of awareness and deeper knowledge about how to do financial management rationally, easy to implement, effective and efficient, as well as being able to apply the theory of proportional percentage of financial planning in two different currencies. So that our targets can maintain their good economic stability during taking overseas study.